Investigating Teachers’ and Educational Leaders’ Perceptions and Practices on the Effectiveness of a Teacher-led Professional Development Model in Abu Dhabi Private Schools - Al Allaq, Khayal (2020)
In view of growing emphasis in the field of education world-wide, and particularly in the United Arab Emirates, there is a strong demand for the refinement of instructional practices through practical and effective professional development. Teacher-led Professional Development (TLPD) is implemented by teachers in the field, rather than by external practitioners. It involves collaborative and reflective meetings, peer observation, and the cooperative refinement and implementation of strategies. This study investigated educators’ perceptions of the value of TLPD, and explored their notions on its impactful instructional benefits. In a sequential mixed-methods approach, data were first collected via a questionnaire from 305 educators from private schools in Abu Dhabi and Al Ain. Then classroom observations, semi-structured interviews and document analysis yielded qualitative data. The findings revealed that teachers perceive TLPD to be effective for: 1) collaboration; 2) meeting school-wide priorities; 3) building leadership capacity; and 4) creating professional learning communities; thus 5) consolidating effective school leadership. These findings may offer principals, policymakers and teachers’ solid insights into establishing a professional learning programme that contributes to effective reform, with practical and immediate advancement in pedagogy, positively impacting the educational process in the UAE and world-wide.